2014
DOI: 10.1186/cc13826
|View full text |Cite
|
Sign up to set email alerts
|

The impact of heatwaves on emergency department visits in Brisbane, Australia: a time series study

Abstract: IntroductionThe acute health effects of heatwaves in a subtropical climate and their impact on emergency departments (ED) are not well known. The purpose of this study is to examine overt heat-related presentations to EDs associated with heatwaves in Brisbane.MethodsData were obtained for the summer seasons (December to February) from 2000–2012. Heatwave events were defined as two or more successive days with daily maximum temperature ≥34°C (HWD1) or ≥37°C (HWD2). Poisson generalised additive model was used to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
44
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(49 citation statements)
references
References 40 publications
5
44
0
Order By: Relevance
“…These studies have found a 'U shaped' distribution of mortality or health service demand, as related to ambient temperature of the day. 5,15,23,24 The findings of this current study build on these studies in demonstrating a clear dose-response relationship for heatwave and health service demand. Note: The error bars represent the 95% CI for the rate ratio.…”
Section: Discussionsupporting
confidence: 63%
“…These studies have found a 'U shaped' distribution of mortality or health service demand, as related to ambient temperature of the day. 5,15,23,24 The findings of this current study build on these studies in demonstrating a clear dose-response relationship for heatwave and health service demand. Note: The error bars represent the 95% CI for the rate ratio.…”
Section: Discussionsupporting
confidence: 63%
“…The importance of SES in the evaluation of effects of HW was highlighted in several studies of vulnerability to HW (11, 28). Overall, populations with lower SES, poor accessibility to services, and older or younger age groups have higher vulnerability to HWs.…”
Section: Discussionmentioning
confidence: 99%
“…In the USA, Basu et al found that increased temperatures had same-day effects on ED visits and age seemed to modify some of these impacts [ 10 ]. In Australia, Toloo et al found emergency departments significantly increased on heatwave days and the RRs in different age groups ranged between 3.0 ~ 9.2 when two or more successive days with daily maximum temperature was ≥34°C [ 28 ]. In Shanghai, Sun et al found heat wave with intensity above the 90 th percentile had 2.62% and 0.95% increases in ED visits for a duration of at least 2 days and 3 days respectively [ 25 ].…”
Section: Discussionmentioning
confidence: 99%